Financial Market Misconduct and Public Enforcement: The Case of Libor Manipulation - Gandhi, Priyank; Golez, Benjamin; Jackwerth, Jens Carsten; Plazzi, Alberto (Management Science, 2019)
Using comprehensive data on London Interbank Offer Rate (Libor) submissions from 2001 through 2012, we provide evidence consistent with banks manipulating Libor to profit from Libor-related positions and to signal their creditworthiness during distressed times. Evidence of manipulation is stronger for banks that were eventually sanctioned by regulators and disappears for all banks in the aftermath of the Libor investigations that began in 2010. Our findings suggest that the threat of large penalties and the loss of reputation that accompany public enforcement can be effective in deterring financial market misconduct. This paper was accepted by Adams, Renee, finance.